2016
DOI: 10.1136/jclinpath-2016-204031
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNA-21 and epithelial mesenchymal transition (EMT) process in colorectal cancer

Abstract: Our data suggest that miRNA-21 in association with E-cadherin and snail-1 does not play a significant role in the development and progression of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Some miRNAs have been observed to be dysregulated in CRC tissues (35). The function of miRNAs in CRC involves controlling EMT (36) and affecting cell proliferation, migration and invasion (37), similar to the function of lncRNAs in CRC. In ovarian cancer, the miRNA-lncRNA signature is important in patient survival (38).…”
Section: Discussionmentioning
confidence: 96%
“…Some miRNAs have been observed to be dysregulated in CRC tissues (35). The function of miRNAs in CRC involves controlling EMT (36) and affecting cell proliferation, migration and invasion (37), similar to the function of lncRNAs in CRC. In ovarian cancer, the miRNA-lncRNA signature is important in patient survival (38).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies reported that the overexpression of miR‐21 is associated with the invasion and metastasis of various human cancer cells . Therefore, in order to determine whether miR‐21‐3p was necessary for cell invasion and migration, transwell assay and wound healing assay were performed to detect the invasive as well as migratory abilities of the HCT116 cells, respectively, following transfection with miR‐21‐3p inhibitors or NC‐miRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Although accumulating evidence supports miR‐21‐5p as 1 mature miR‐21 strand that is overexpressed in many cancers, and plays a role in the processes of carcinogenesis and metastasis, studies regarding the biological role of the other miR‐21 passenger strand, miR‐21‐3p, in CRC cells are limited. The comprehensive understanding of CRC at molecular and cellular levels is still urgently needed to help reduce the incidence and to improve the survival rate of CRC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an in vitro assay involving Transwell plates revealed that miR-650 promotes HCC cell migration and invasion. There is accumulating evidence that miRNAs have a crucial function related to the progression of HCC EMT [19,20]. Considering the EMT is a wellknown basal mechanism related to cancer cell migration and invasion [3], we speculated that miR-650 may influence HCC EMT.…”
Section: Discussionmentioning
confidence: 97%